Learning while teaching : embracing a collaborative action-research project - Leal, Susana Mira (2011)
In a context of swift and continuous scientific, technological, socio-economical and environmental change, teachers must become more and more aware of the complexity of the educational process and continually analyze their actions, responsibilities and roles. Commonly, teachers regret the scarcity and inadequacy of lifelong training programs, the time they involve and the gap between theory and practice. They must understand they can better meet the educational challenges they face if they engage in collaborative research projects. One of the greatest challenges teachers face daily has to do with students' lack of interest in learning what society thinks they should learn. In this paper, we present some data from a research project (Research for a Relevant Curriculum) that illustrates how collaborative action research can help teachers think their practices and improve their teaching skills aiming for their students’ motivation and success (Sousa & Valadão, 2008). RRC is a collaborative action research project developed in the Azores (Portugal). It involves twelve teachers of basic education from two islands of the Archipelago (São Miguel and Terceira) and four researchers from the University of Azores. In 2009, RRC established an international partnership with teachers and researchers from Bucharest, Romania (ENCUR), and, in July, 2010, organized the first Portuguese-Romanian Colloquium on Curriculum Issues, which took place in Terceira, Azores. The second edition is already being prepared and will take place in 2011, in Bucharest.